Regulatory Limits of Empowering Biogas Digester Integrated with Indonesia’s Local Wisdom - Listiningrum, Prischa; Maheswara, Ida Bagus Ayodya; Wahyuni, Herlin Sri; Vibhu, Avanish (University of Jember, 2023)
This paper analyses the international and domestic regulatory framework for managing waste-to-energy in Indonesia’s rural areas to support climate mitigation. The countryside is known to be the most significant contributor to organic waste due to the high productivity of the agricultural and livestock sectors. In contrast, organic waste is left without proper management and contributes to global greenhouse gas emissions. Indonesia has agreed to contribute to the Paris Agreement to reduce emissions by 29% in 2030 or 41% with international assistance, but its follow-up to switch to renewable energy appears insufficient. This study uses a socio-legal approach to unpack the waste-to-energy problems in one of Indonesia's villages: Tawangsari Village, Pujon District, Malang Regency, East Java Province. The study results reveal that the biogas program launched by the government through the